2021
DOI: 10.3389/fphar.2021.626267
|View full text |Cite
|
Sign up to set email alerts
|

Systems Pharmacology Approach and Experiment Evaluation Reveal Multidimensional Treatment Strategy of LiangXueJieDu Formula for Psoriasis

Abstract: Clinical studies have demonstrated the anti-psoriatic effect of the LiangXueJieDu (LXJD) herbal formula. However, the systemic mechanism and the targets of the LXJD formula have not yet been elucidated. In the present study, a systems pharmacology approach, metabolomics, and experimental evaluation were employed. First, by systematic absorption-distribution-metabolism-excretion (ADME) analysis, 144 active compounds with satisfactory pharmacokinetic properties were identified from 12 herbs of LXJD formula using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Many elements in the glycerol phospholipid metabolism pathway, such as PA, PC, and PI, have also been confirmed to undergo significant changes in the plasma of psoriasis patients ( 4 ). Drugs such (R)-salbutamol and Chinese Herbal formula can alleviate psoriasis by improving glycophoric metabolism ( 83 , 84 ). Arachidonic acid (AA) is a polyunsaturated fatty acid that serves as a precursor to various bioactive lipid mediators, including prostaglandins, leukotrienes, and thromboxanes.…”
Section: Discussionmentioning
confidence: 99%
“…Many elements in the glycerol phospholipid metabolism pathway, such as PA, PC, and PI, have also been confirmed to undergo significant changes in the plasma of psoriasis patients ( 4 ). Drugs such (R)-salbutamol and Chinese Herbal formula can alleviate psoriasis by improving glycophoric metabolism ( 83 , 84 ). Arachidonic acid (AA) is a polyunsaturated fatty acid that serves as a precursor to various bioactive lipid mediators, including prostaglandins, leukotrienes, and thromboxanes.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [28] GC-MS Zhao et al [37] UPLC/Q-TOF-MS 13 PV of treatment responders with the LiangXueJieDu formula Serum Disturbed glycerophospholipid metabolism and steroid hormone biosynthesis were reversed using the LiangXueJieDu formula treatment.…”
Section: Kishikawamentioning
confidence: 99%
“…Similarly, Zhao et al [ 37 ] illustrated the anti-psoriatic effectiveness of the LiangXueJieDu formula, a Chinese herbal medicine, using metabolomics. They analyzed metabolic changes in serum of psoriasis patients after an 8-week treatment and found that disrupted glycerophospholipid metabolism and steroid hormone biosynthesis could be reversed by treatment with the LiangXueJieDu formula.…”
Section: Metabolomics For Explaining the Mechanism Of Treatments And ...mentioning
confidence: 99%
“…Taking the herbs (Jinyinhua, Lianqiao, Jiegeng, Bohe, Dantouchi, Danzhuye, Niubangzi, Jingjie, Lugen, and Gancao) in YQS as keywords, the TCMSP database (http://tcmspw.com/tcmsp.php) was used to retrieve their relevant chemical compositions, and oral bioavailability (OB) ≥ 30%, drug-likeness (DL) ≥ 0.18, and drug half-life (HL) ≥ 4 h were adopted as screening conditions to obtain active ingredients that meet the conditions [14][15][16]. Among them, the active ingredients of Danzhuye were obtained through a combination of a literature search [17] and the TCMSP database.…”
Section: Finding Potential Targets Of Yqsmentioning
confidence: 99%